The Fabulousness and the Fury: Preparing for a Drag Queen Storytime - Davey, Douglas (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
After announcing the launch of a Drag Queen Storytime, the Halton Hills Public Library (HHPL) received positive feedback from the community, but also faced criticism from a small but vocal group of citizens. Complaints reached as high as the mayoral office, challenging the library’s position as a trusted community institution, and testing the rigour of its training, communications, policies, and procedures. Despite the pushback, the library ran a highly successful program and afterward redoubled its commitment to fighting homophobia and promoting equality. This article details how the HHPL came to offer the program, what the response was, as well as suggestions for measuring success and processing complaints.